2021
DOI: 10.1007/s40617-020-00490-3
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of “Balance”: a Home-Based, Parent-Implemented Program Addressing Emerging Problem Behavior

Abstract: Programs that prevent the development of severe problem behavior in young children with autism spectrum disorder (ASD) are critically needed. We describe a program designed to do this, and we report on a preliminary evaluation of its effects with four 3and 4-year-old children with ASD. Parents served as the primary implementers, with twice-weekly coaching from a Board Certified Behavior Analyst. Direct measures and Aberrant Behavior Checklist scores reflected decreases in emerging problem behavior. Direct meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Of note, one study ( 63) included a sample that partially overlapped with two other studies (60,64). A seventh study explicitly integrated FCT within a broader behavior analytic package for behaviors like whining, yelling, aggression, and throwing items (71). Five studies employing behavior analytic methodologies to decrease the rate or frequency of child challenging behaviors also targeted language or social communication (57,60,61,70,71).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, one study ( 63) included a sample that partially overlapped with two other studies (60,64). A seventh study explicitly integrated FCT within a broader behavior analytic package for behaviors like whining, yelling, aggression, and throwing items (71). Five studies employing behavior analytic methodologies to decrease the rate or frequency of child challenging behaviors also targeted language or social communication (57,60,61,70,71).…”
Section: Resultsmentioning
confidence: 99%
“…Their results found that the textual analysis method was less likely to result in bias but the thematic analysis resulted in questions that were valued as more important to the participants. Although several experiments in the current review did provide multiple data collection methods (Hong et al., 2018; Pisman & Luczynski, 2020; Robertson, 2016; Ruppel et al., 2021) it is important that future research continue to evaluate additional development methods similar to the research of Anderson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although several experiments in the current review did provide multiple data collection methods (Hong et al, 2018;Pisman & Luczynski, 2020;Robertson, 2016;Ruppel et al, 2021) it is important that future research continue to evaluate additional development methods similar to the research of Anderson et al…”
Section: Discussionmentioning
confidence: 99%
“…Thus, preventing the problem behavior of autistic children is often regarded as a top priority by stakeholders (Sugai & Horner, 2008). Ruppel et al (2021) evaluated a home-based prevention program called Balance, which was implemented by caregivers and taught communication and self-control 1 skills. Children who participated were at risk for 1 Various scientific fields have described self-control responses as alternatives to socially problematic behavior (e.g., alcohol use disorder, Carpenter et al, 1985;antisocial behavior, Delisi et al, 2011;hitting others, Luczynski & Hanley, 2013;risk taking, Romer et al, 2010).…”
mentioning
confidence: 99%